Strategy and Function of Perfect Health's Public Relations Activities in Enhancing a Positive Image through Philanthropic Corporate Social Responsibility - Geofakta Razali; Rizki Hidayat (Ikatan Sarjana Komunikasi Indonesia, 2022)
Efforts to reduce poverty rate are still a highlighted issue almost in every country. Especially during the COVID-19 pandemic, there is increasing attention to corporate social responsibility (CSR) around the world, to find out the magnitude of its influence on corporate image as can be seen from its sustainable, accountable and transparent implementation. Perfect Health carries out several strategies to realize the function of Public Relations activities through CSR Philanthropy in the program